Relationship between features of spokes-character and brand trust of consumers - Bidin, Hernani (2018)
The trend of using spokes-character has developed in various promotional campaigns over the past century. As an animated being or animated object that is used to promote a product, service, or idea, spokes-character must be used consistently in conjunction with a product over time. Spokes–character are used to create unique brand or company images, and to stand for the brand. To address this situation, organizations gain revenue by promoting more campaigns using potential spokes-character and keeping good relationship with consumers. Strategizing the features of spokescharacter for brand trust is among the effective tools in promoting and maintaining relationship with consumers. This research is developed to construct an understanding of the advantages of using spokes-characters advertising for communication in Malaysia. There are still some research gaps in the past studies and pointed out that popular spokes-character are capable of enhancing consumer preference for a brand but fail to describe the mechanism by which the features towards spokes-character influences the brand preference. The general purpose of this study is to investigate the relationship between features of spokes-character and the brand trust of consumers. To achieve the said objective, six features of spokes-character are tested, namely Expertise, Relevance, Nostalgia, Personality, Physical Characteristics and Humor. This study employed the quantitative method of data collection. The statistical analysis used includes descriptive statistics, correlation and regression analysis. Data were obtained through a survey questionnaire from 400 undergraduates from four high ranked local universities in Selangor. Self-administered questionnaires were sent and personally collected by the researcher. All data were gathered and coded using Statistical Package for Social Science (SPSS 22.0), a statistical computer program. The findings analysis throughout the multiple regression was found that there were only three features of spokes-character which most contributed towards brand trust, namely Personality, Physical Characteristics and Expertise. The results indicated that, Personality has given the significant results. So did the combination of Personality and Physical Characteristics, also provided the significant results. And lastly, when Personality, Physical Characteristics and Expertise were merged all together also contributed the significant results.